Fashion Branding: Upaya Diferensiasi Produk dan Unique Selling Point Merek Bertjorak - Arinda, Syafa; Lubis, Evawani Elisa; Rimayanti, Nita (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2025)
This research discusses branding strategies and Unique Selling Points (USP) as important elements in forming the Bertjorak brand image, which is inspired by Indonesian culture through a combination of eccentric colors in its products. Using qualitative methods, this research collects data through interviews, observation and documentation. The research results show that Bertjorak successfully implemented a co-branding strategy through collaboration with singer Basboi in the project